Neuropeptides as regulators of bone metabolism: from molecular mechanisms to traditional Chinese medicine intervention strategies - Lin, Qing; Zhao, Biyi; Huang, Jiajia; Chen, Rumeng; Sun, Weipeng; Ye, Qianyun; Yang, Li; Zhu, Xiaofeng; Li, Xiaoyun; Zhang, Ronghua (Frontiers in Pharmacology, 2025)
Osteoporosis (OP) is a complex bone metabolism disorder disease that affects the skeleton, nervous system, muscles, and multiple tissues. Neuropeptides, which are endogenous substances derived from both bone and brain, play a critical role in maintaining the balance of bone metabolism. This review summarizes research conducted from 1986 to 2024 on the pathological mechanisms of neuropeptides and their receptors in the context of OP. Specifically, the roles of Neuropeptide Y, Vasoactive Intestinal Peptide, Calcitonin Gene-Related Peptide, and Substance P and their receptors in key processes of OP were examined, including their function of bone formation and resorption, osteoblast differentiation, and osteoclast differentiation. Our study showed that these neuropeptides could promote bone formation and inhibit bone resorption, while their receptors in osteocytes exhibit distinct functions, indicating complex regulatory mechanisms that require further investigation. Additionally, we summarize the progress of Traditional Chinese Medicine (TCM) formulae, single TCM herbs, and bioactive compounds derived from TCM in exerting anti-OP effects through neuropeptide modulation. These studies highlight the multi-targeted and multi-mechanistic pharmacological actions of TCM in treating OP. By integrating these findings, we aim to enhance the understanding of neuropeptides’ roles in bone metabolism and to explore the development of neuropeptide-targeted TCM therapies for OP management. This comprehensive perspective highlights the potential of neuropeptides as therapeutic targets, paving the way for innovative approaches to treating OP.